Dietary adaptations and nutritional shift of Alpine musk deer in Helan mountains, north China - Zhi-Rong Zhang; Chang Zhao; Yun Su; Bao-Jun Zhang; Wen-Jun Zhang; Jing Meng; Kuo-Cheng Lv; Yang Lu; Meng-Qi Ding; Li-Wei Teng; Zhen-Sheng Liu (Global Ecology and Conservation, 2025)
The Alpine musk deer (Moschus chrysogaster), an endangered species with fewer than 200 individuals in fragmented habitats of the Helan mountains, faces pronounced seasonal resource fluctuations. This study investigates seasonal shifts in diet composition, nutrient intake, and tolerance to secondary plant metabolites via fecal microhistological and feed proximate analyses conducted from 2014 to 2016. In summer, the diet included 31 plant species, dominated by mosses (18.15 %), Prunus sibirica (11.32 %), and Salix spp. (10.94 %), whereas winter diets of 30 species shifted toward woody and herbaceous plants such as Lonicera edulis (13.68 %) and Astragalus chingianus (11.33 %), with complete exclusion of mosses. Significant seasonal variations were observed in the Water (W) and Crude ash (CA) content, with higher levels recorded in summer. The relative density of food intake was significantly positively correlated with CA in summer and with Ether extract (EE) in winter. Response surface models revealed specific seasonal foraging patterns: in winter, musk deer prefer high-energy and high-protein foods, with tolerance to higher tannin level, while in summer, they favor low-protein and high-tannin foods, irrespective of energy content. These findings highlight the adaptive capacity of Alpine musk deer to cope with seasonal resource fluctuations in Helan mountains, contributing to their survival and reproductive success, and thus inform conservation strategies that emphasize habitat connectivity and protection of critical foraging areas to ensure long-term viability.